Evangelical Participation in Brazilian Politics And its Identification With Right Governments - Proença, Wander de Lara (Revista Relegens Thréskeia, 2021)
The last elections in Brazil have shown a growing participation of evangelicals in the political scenario and a majority identification with right-wing governments. A representative mark of this behavior occurred in the expressive support given to the presidential election of Bolsonaro and in the occupation of several positions in the exercise of his government. The article presents the historical trajectory of evangelical behavior in the political sphere and also the factors that historically configure theimagery of this religious segment, guiding its approaches to the right. Priority is given to the conceptual notion of “imaginary”, as used by the so-called new political history. As sources of analysis, in addition to bibliographic texts, audiovisual resources, social media and lyrics from the Brazilian evangelical universe are used.